Restoration of degraded rangeland by the use of Cenchrus ciliaris, a high value perennial forage grass, in Hail region (Saudi Arabia) - Mseddi K.; Shammari A.; Dghimen M.; Abdallah L. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Saudi Arabia (KSA) is one of the countries that suffers from the degradation of natural rangelands aggravated by severe drought. Rangelands with wild forage species decreased and refuged in difficult accessible zones such as mountains and deep Wadi. Cenchrus ciliaris L., a high value pasture plant of the Saudi Arabian mountains, is one of the endangered species that becomes very rare in its natural habitats. In this work five accessions of Cenchrus ciliaris were collected from different zones in Hail region (North of KSA), to select the most vigorous ecotypes to be introduced in the degraded lands. In the first part of this study, the germination capacities of different accessions were estimated. The second part focuses on the study of the vegetative vigour of different accessions by the assessment of morphological parameters. In the last part of this study, a selection of the resistant accessions to overgrazing by a protocol of repeated cuts, was conducted. This study permitted to select the most productive and drought tolerant accessions of Cenchrus ciliaris.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)